Question
upstudy study bank question image url

\( \begin{array}{l}f(3)=2 f^{\prime}(3)=4 \\ \text { and } \\ g^{\prime}(3)=-3 g(3)=9\end{array} \rightarrow\left(\frac{f}{g}-f\right)^{\prime}(3)= \) ?

Ask by Patel Sandoval. in Iran
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The derivative of \(\left(\frac{f}{g}-f\right)\) at \(x=3\) is \(-\frac{94}{27}\).

Solution

To find the derivative of the expression \(\left(\frac{f}{g}-f\right)\) at \(x=3\), we can use the quotient rule and the sum rule of differentiation. Given: \( f(3) = 2 \) \( f'(3) = 4 \) \( g'(3) = -3 \) \( g(3) = 9 \) Let's find the derivative of \(\frac{f}{g}\) at \(x=3\) first: \[ \left(\frac{f}{g}\right)'(3) = \frac{f'(3)g(3) - f(3)g'(3)}{(g(3))^2} \] Substitute the given values: \[ \left(\frac{f}{g}\right)'(3) = \frac{4 \cdot 9 - 2 \cdot (-3)}{9^2} = \frac{36 + 6}{81} = \frac{42}{81} \] Now, let's find the derivative of \(-f\) at \(x=3\): \[ (-f)'(3) = -f'(3) = -4 \] Finally, we can find the derivative of \(\left(\frac{f}{g}-f\right)\) at \(x=3\) by adding the derivatives of \(\frac{f}{g}\) and \(-f\): \[ \left(\frac{f}{g}-f\right)'(3) = \left(\frac{f}{g}\right)'(3) + (-f)'(3) = \frac{42}{81} - 4 \] Let's calculate the final result. Calculate the value by following steps: - step0: Calculate: \(\frac{42}{81}-4\) - step1: Reduce the fraction: \(\frac{14}{27}-4\) - step2: Reduce fractions to a common denominator: \(\frac{14}{27}-\frac{4\times 27}{27}\) - step3: Transform the expression: \(\frac{14-4\times 27}{27}\) - step4: Multiply the numbers: \(\frac{14-108}{27}\) - step5: Subtract the numbers: \(\frac{-94}{27}\) - step6: Rewrite the fraction: \(-\frac{94}{27}\) The derivative of \(\left(\frac{f}{g}-f\right)\) at \(x=3\) is \(-\frac{94}{27}\) or \(-3\frac{13}{27}\) or \(-3.4881\).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To find the derivative of \( \left(\frac{f}{g} - f\right) \) at \( x=3 \), we can start by applying the quotient rule and then simplifying. The first part is the derivative of the quotient: \[ \left( \frac{f}{g} \right)' = \frac{f'g - fg'}{g^2} \] Now substituting the known values at \( x=3 \): 1. \( f(3) = 2 \) 2. \( g(3) = 9 \) 3. \( f'(3) = 4 \) 4. \( g'(3) = -3 \) Plug these values into the derivative: \[ \left( \frac{f}{g} \right)'(3) = \frac{(4)(9) - (2)(-3)}{9^2} = \frac{36 + 6}{81} = \frac{42}{81} = \frac{14}{27} \] Now we find the derivative of \( -f \): \[ (-f)'(3) = -f'(3) = -4 \] Now combine these results to find \( \left( \frac{f}{g} - f \right)'(3) \): \[ \left( \frac{f}{g} - f \right)'(3) = \left( \frac{f}{g} \right)'(3) - (-f)'(3) = \frac{14}{27} - 4 \] To subtract, express 4 with a common denominator: \[ 4 = \frac{108}{27} \] Thus, we have: \[ \frac{14}{27} - \frac{108}{27} = \frac{14 - 108}{27} = \frac{-94}{27} \] Therefore, the final answer is: \[ \left(\frac{f}{g} - f\right)^{\prime}(3) = \frac{-94}{27} \]

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy